Voices on the Move: A Critical Analysis of Public Vehicle Literature in Nepal (KMC Journal, 2025)
Public texts written on vehicles are not merely cosmetic but powerful tools for communicating diverse identities and ideologies. This qualitative research investigates common themes or contents written on Nepali vehicles, and analyzes them at the textual, discursive, and sociocultural levels based on Fairclough’s (1995) critical discourse analysis (CDA). Twenty eight photographs of vehicle texts were purposively selected as samples for the study. Among them, twenty four photographs were captured using my iPhone during my travels across various locations in Nepal, while four photographs were collected from social media. The study reveals the vehicle literature conveys messages about identity, life struggles, socioeconomic commentary, philosophy of life and reflections, humour and satire, politics and government, and romance and teasing. Textually, the vehicle literature comprises poetry, prose, slogans, verses, phrases, and sentences, enriched with literary devices like irony, metaphor, parallelism, hyperbole, satire, contrast, personification, and symbolism. These features discursively illustrate how literary features integrate into vehicle literature, positioning vehicles in Nepal as mobile platforms for creative linguistic and literary expressions, echoing societal discourses. The writings socioculturally expose cultural, political, economic, religious, and gender-based ideologies. The study concludes that public vehicles serve as linguistic spaces for public messaging, self-expression, emotional release, and critique, providing insights into lifestyles, values, and admiration, while promoting cultural and ideological narratives. Pedagogically, vehicle literature offers valuable resources for teaching linguistic and literary features while fostering cultural awareness, and creative and critical thinking skills.